PEMBINAAN KENAKALAN ANAK OLEH YAYASAN SINAI DI SUKOHARJO - Agustin Fatikasari; Supriyadi Supriyadi (Universitas Sebelas Maret (UNS), 2019)
Juvenile delinquency is getting more worrying in both developed and developing countries over times. Juvenile delinquency is also a problem with which any family often complains. One of attempts to be taken to deal with juvenile delinquency is to conduct rehabilitation or mentoring. This research aimed to analyze the type of juvenile delinquency and its cause, to find out the form of building and the factors supporting and inhibiting the mentoring. This research employed Max Weber’s Social Action theory. This qualitative research with case study was conducted in Sukoharjo. The sampling technique employed was purposive sampling technique. The informant of research consists of Chairperson and Mentors of Children in SINAI Foundation of Sukoharjo, and children who have ever committed delinquency and live in SINAI Foundation. Data was collected through observation, in-depth interview, and documentation. To validate the data, source triangulation was used. Technique of analyzing data used was Miles and Huberman’s interactive analysis model. The result of research showed that type of delinquency committed by children residing SINAI Foundation is non-conform action including escaping from home or foundation and playing truant, and antisocial or asocial action including not paying transportation ticket or cost when going by public transportation and large vehicles crossing the road. The cause of delinquency committed by children residing SINAI Foundation included internal and external factors. Internal factor included wish coming from inside. External factor included family environment, economic condition, and friendship environment. The form of children mentoring conducted by SINAI foundation included mental spiritual building, skill building, and discipline building. The factor supporting the mentor was a belief inside assuming that mentoring the needy children was the form of worship to God and that fellow human beings should help each other. Meanwhile the factors supporting the child to attend the mentoring were the presence of complete and feasible facilities for residence and the fulfilled daily need, the access to education and the presence of friends or relatives living there. The factor inhibiting the Mentor included queer SINAI Foundation resident’s queer behavior and sometimes accident occurring during mentoring or treatment. The factor inhibiting the children attending the mentoring was the Mentor’s resoluteness making them sometimes upset and longing for seeing their parents.